Effects of Knowledge of Results Frequency on the Learning of Generalized Motor Programs and Parameters under Conditions of Constant Practice. Issue 1 (August 2014) - Albuquerque, Maicon R.; Lage, Guilherme M.; Ugrinowitsch, Herbert; Corrêa, Umberto C.; Benda, Rodolfo N.
The present study investigated the effects of the frequency of knowledge of results (KR) on both generalized motor programs and parameters. Two experiments were conducted that compared two frequencies of KR in terms of generalized motor programs and parameters: (1) the first experiment compared the effects of KR frequency on generalized motor programs in the 100% and 50% groups; and (2) the second experiment compared the effects of reduced KR frequency on parameters in the 100% and 50% groups. In the first experiment, results showed that the 50% group exhibited smaller relative timing errors than did the 100% group, but absolute timing errors in the transfer test were similar between these two groups. In the second experiment, both groups exhibited similar relative and absolute timing errors. These results suggested that the beneficial effects of reduced KR frequency were restricted to generalized motor programs.